A new Dionysia (Primulaceae) species from southern Turkey, the most western species of the Irano-Turanian genus - Güzel, Yelda (Phytotaxa, 2021)
A new Dionysia species, D. zeynepiae, is described from Antakya, a Mediterranean province in southern Turkey. It differs from all other known species of the genus by the presence of the trifid corolla lobes (vs. entire, emarginate or bifid lobes). This is the most western and most separated population of this mostly Irano-Turanian genus, which is distributed mainly in the Zagros Mountains (Iran) and adjacent areas. The floral morphology of the heterostylous flowers is also described in detail.